PROFITABILITY OF FOOD AND BEVERAGES COMPANIES IN INDONESIA - Kun Ismawati; Juni Trisnowati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The effectiveness of good management can guarantee a maximum profit through sales and investment. Profitability is one of the tools to assess it. There are not many studies that highlight profitability as proxied by Return in Assets (ROA) and use independent variables in the form of Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Longterm Debt to Equity Ratio (LtDER). Some research about profitability proxied by ROA still showed different results among each other. The purpose of this study was to examine the effect of DAR, DER, and LtDER on ROA on food and beverage companies in Indonesia both partially and simultaneously. Data obtained from the Indonesia Stock Exchange (IDX) in the form of annual financial statements. The research sample included 36 time series data from 9 food and beverage companies during the period of 2016 to 2019. Data analysis using multiple linear regression, t-test, F test, and the coefficient of determination. The result of the study stated: 1) DAR has a negative significant effect on ROA, 2) DER has a negative effect but not significant on ROA, 3) LtDER has a significantly positive effect on ROA, 4) DAR, DER, and LtDER have significantly positive effect on ROA simultaneously. Those results illustrate that the higher ratio of DAR and DER will decrease ROA; on the contrary, the higher LtDER will increase ROA. Those results are important for stakeholders in their decision making process to maximize profits.